IDENTIFIKASI FONEM DALAM MEMBEDAKAN KEMIRIPAN BUNYI UJARAN ANTARA BAHASA DAERAH TERNATE DAN BAHASA DAERAH TIDORE - Muharam, Rijal; Haerul, Haerul; Azzahra, Rizmada; Wahab, Justam S. (Jurnal Bilingual, 2025)
The purpose of this research is to add new knowledge about the form of similarity of speech sounds in communication. This research will broaden the insight and development of linguistics, especially language acquisition, which starts from the dimension of language sounds. However, what is meant is not the type or type of the speech sound but the sound change in the form of a letter or a consonant that makes the word or sentence said to have changed even though when paying attention to the pronunciation it is similar but not the same. The method used in this research is a qualitative method by prioritizing the type of research that is descriptive. The data that has been collected is then verified by analyzing one by one the words or sentences that are said to be similar. Phrases or sentences that experience similarities are reclassified in the form of data collection which words are included in the Ternate regional language and which phrases or sentences are categorized as Tidore regional language. The results showed that the identification of phonemes in distinguishing the similarity of speech sounds that occur between Ternate and Tidore local languages is very much in language activities so that many speakers or people who use these two languages are not able to distinguish which a word or phrase belongs to both categories of local languages.